1995
DOI: 10.1007/bf02259661
|View full text |Cite
|
Sign up to set email alerts
|

Modality dependent changes in event-related potentials correlate with specific cognitive functions in nondemented patients with Parkinson's disease

Abstract: The relationship between event-related potentials (ERPs) and cognitive functioning was studied in patients with Parkinson's Disease (PD) but without dementia. Auditory and visual stimuli were used; 30 subjects participated in the auditory study and 20 in the visual study. Patient groups did not differ with respect to gender, age, education, illness duration, and level of cognitive functioning. Visual stimuli were 2.3 cpd sinusoidal grating patterns randomly presented in an oddball paradigm (oblique vs. vertica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 52 publications
4
23
0
4
Order By: Relevance
“…This restorative effect of levodopa on abnormal and a significant correlation between the P300 latency and P300 in PD has been repeatedly observed by others performances on frontal lobe related cognitive tasks was [21,33]. Prasher and Findley [24] presented the opposite demonstrated in PD patients [7,15,20,22]. Intravenous results showing a significant prolongation of the P300 injection of levodopa produced significant shortening of latency after long-term levodopa therapy in initially de the P300 latency along with increase in regional cerebral novo patients.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This restorative effect of levodopa on abnormal and a significant correlation between the P300 latency and P300 in PD has been repeatedly observed by others performances on frontal lobe related cognitive tasks was [21,33]. Prasher and Findley [24] presented the opposite demonstrated in PD patients [7,15,20,22]. Intravenous results showing a significant prolongation of the P300 injection of levodopa produced significant shortening of latency after long-term levodopa therapy in initially de the P300 latency along with increase in regional cerebral novo patients.…”
Section: Discussionsupporting
confidence: 71%
“…The evoked cognitive potentials in a healthy Cynomolgus hippocampus and associated brain sites have been regarded monkey [3]. Stanzione et al [32] demonstrated that [7][8][9][10][11][12][13][14][15] as a generator of the P300 [14], and the dopamine has been days of levodopa therapy significantly shortened the P300…”
Section: Discussionmentioning
confidence: 99%
“…The degree of global cognitive impairment has been linked to P3b latency by studies showing correlations between P3b latency and neuropsychological measures of general intelligence (Bodis-Wollner et al, 1995;Hansch et al, 1982;Katsarou et al, 2004), processing speed (O'Donnell et al, 1987), and, most frequently, the global score on the MMSE (Lukhanina et al, 2009;Maeshima et al, 2002;Matsui et al, 2007;Sartucci et al, 1990;Stamenović et al, 2005;Tachibana et al, 1997; but see Elwan et al, 1996;Lukhanina et al, 2008).…”
Section: P3b and The Specificity Of Cognitive Changes In Pdmentioning
confidence: 99%
“…Nowadays ERPs are being more commonly used to evaluate quantitatively the cognitive functions in different disease states [20,21,22]. ERPs are those potentials of the EEG which are evoked by the preparation of or for events, and they include an early sensory evoked potential and a late (cognitive) response P300 component [23].…”
Section: Introductionmentioning
confidence: 99%